Climate impacts on vegetation and fire dynamics since the last deglaciation at Moossee (Switzerland) - F. Rey; F. Rey; F. Rey; E. Gobet; E. Gobet; C. Schwörer; C. Schwörer; A. Hafner; A. Hafner; S. Szidat; S. Szidat; W. Tinner; et al. (Climate of the Past, 2020)
Since the Last Glacial Maximum (LGM; end ca. 19 000 cal BP) central European plant communities have been shaped by changing climatic and anthropogenic disturbances. Understanding long-term ecosystem reorganizations in response to past environmental changes is crucial to draw conclusions about the impact of future climate change. So far, it has been difficult to address the post-deglaciation timing and ecosystem dynamics due to a lack of well-dated and continuous sediment sequences covering the entire period after the LGM. Here, we present a new paleoecological study with exceptional chronological time control using pollen, spores and microscopic charcoal from Moossee (Swiss Plateau, 521 m a.s.l.) to reconstruct the vegetation and fire history over the last ca. 19 000 years. After lake formation in response to deglaciation, five major pollen-inferred ecosystem rearrangements occurred at ca. 18 800 cal BP (establishment of steppe tundra), 16 000 cal BP (spread of shrub tundra), 14 600 cal BP (expansion of boreal forests), 11 600 cal BP (establishment of the first temperate deciduous tree stands composed of, e.g., Quercus, Ulmus, Alnus) and 8200 cal BP (first occurrence of mesophilous Fagus sylvatica trees). These vegetation shifts were caused by climate changes at ca. 19 000, 16 000, 14 700, 11 700 and 8200 cal BP. Vegetation responses occurred with no apparent time lag to climate change when the mutual chronological uncertainties are considered. This finding is in agreement with further evidence from southern and central Europe and might be explained by the proximity to the refugia of boreal and temperate trees (<400 km) and rapid species spreads. Our palynological record sets the beginning of millennial-scale land use with periodically increased fire and agricultural activities of the Neolithic period at ca. 7000 cal BP. Subsequently, humans rather than climate triggered changes in vegetation composition and structure. We conclude that Fagus sylvatica forests were resilient to long-term anthropogenic and climatic impacts of the Mid and the Late Holocene. However, future climate warming and in particular declining moisture availability may cause unprecedented reorganizations of central European beech-dominated forest ecosystems.